Comparison of In Situ and Postsynthetic Formation of MOF-Carbon Composites as Electrocatalysts for the Alkaline Oxygen Evolution Reaction (OER) - Linda Sondermann; Laura Maria Voggenauer; Annette Vollrath; Till Strothmann; Christoph Janiak (Molecules)
Mixed-metal nickel-iron, NixFe materials draw attention as affordable earth-abundant electrocatalysts for the oxygen evolution reaction (OER). Here, nickel and mixed-metal nickel-iron metal–organic framework (MOF) composites with the carbon materials ketjenblack (KB) or carbon nanotubes (CNT) were synthesized in situ in a one-pot solvothermal reaction. As a direct comparison to these in situ synthesized composites, the neat MOFs were postsynthetically mixed by grinding with KB or CNT, to generate physical mixture composites. The in situ and postsynthetic MOF/carbon samples were comparatively tested as (pre-)catalysts for the OER, and most of them outperformed the RuO2 benchmark. Depending on the carbon material and metal ratio, the in situ or postsynthetic composites performed better, showing that the method to generate the composite can influence the OER activity. The best material Ni5Fe-CNT was synthesized in situ and achieved an overpotential (η) of 301 mV (RuO2 η = 354 mV), a Tafel slope (b) of 58 mV/dec (RuO2 b = 91 mV/dec), a charge transfer resistance (Rct) of 7 Ω (RuO2 Rct = 39 Ω), and a faradaic efficiency (FE) of 95% (RuO2 FE = 91%). Structural changes in the materials could be seen through a stability test in the alkaline electrolyte, and chronopotentiometry over 12 h showed that the derived electrocatalysts and RuO2 have good stability.